Revision of the taxonomic rank of Armada barrygoateri Fibiger et Ronkay, 2003 (Lepidoptera: Noctuidae: Acontiinae) - A.Yu. Matov; A.N. Poltavsky; P.N. Korzhov (Кавказский энтомологический бюллетень, 2021)
In 2019 and 2020, the population of Armada Staudinger, 1884 represented by specimens with light colouration of forewings (identical with this in Armada clio (Staudinger, 1884)) and with dark colouration (as in Armada barrygoateri Fibiger et Ronkay, 2003) was found in Stavropol Region of Russia. Study of genitalia of males and females with various colouration of forewings showed that all specimens belong to one species. Comparison of the females with the holotype of A. barrygoateri, described by a single female, and comparison of male genitalia with those of a topotype of A. clio showed the absence of clear differences between A. clio and A. barrygoateri, therefore the taxonomic rank of A. barrygoateri was changed to the subspecies, Armada clio barrygoateri stat. n., with the range limited by semideserts of Ciscaucasia.